Cup orientation following posterior approach THA: the effect of different visual aids and pelvic supports - Innmann, Moritz Maximilian; Verhaegen, Jeroen; Merle, Christian; Beaulé, Paul E.; Meermans, Geert; Grammatopoulos, George (BMC musculoskeletal disorders, 2022)
This study aims to compare cup inclination achieved (1) Using two orientation guides, whilst using the same 3-point pelvic positioner and (2) Using two types of pelvic positioners, whilst measuring intra-operative cup inclination with an inclinometer.
Gesehen am 25.10.2022